If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + (a + -3) = (a + -4) + -1(a + 1) Reorder the terms: a + (-3 + a) = (a + -4) + -1(a + 1) Remove parenthesis around (-3 + a) a + -3 + a = (a + -4) + -1(a + 1) Reorder the terms: -3 + a + a = (a + -4) + -1(a + 1) Combine like terms: a + a = 2a -3 + 2a = (a + -4) + -1(a + 1) Reorder the terms: -3 + 2a = (-4 + a) + -1(a + 1) Remove parenthesis around (-4 + a) -3 + 2a = -4 + a + -1(a + 1) Reorder the terms: -3 + 2a = -4 + a + -1(1 + a) -3 + 2a = -4 + a + (1 * -1 + a * -1) -3 + 2a = -4 + a + (-1 + -1a) Reorder the terms: -3 + 2a = -4 + -1 + a + -1a Combine like terms: -4 + -1 = -5 -3 + 2a = -5 + a + -1a Combine like terms: a + -1a = 0 -3 + 2a = -5 + 0 -3 + 2a = -5 Solving -3 + 2a = -5 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2a = -5 + 3 Combine like terms: -3 + 3 = 0 0 + 2a = -5 + 3 2a = -5 + 3 Combine like terms: -5 + 3 = -2 2a = -2 Divide each side by '2'. a = -1 Simplifying a = -1
| x^2+3(3x-4)-2x(6+2x)=0 | | 20=3.1-5.1b | | 6x-x+12=10x+7 | | 3t^2+5t=0 | | 11=-4.9-y | | 3c^2-17c-6= | | 2(3+3x)-2=16 | | 4x^2+9-12x=0 | | -5+6x+2x=43 | | 4x2+9-12x=0 | | 7x+20=6x+23 | | 7(2p+1)=44.5-p | | 8x-11=21+4x | | -x+14=6x-7 | | 3(2x+5)=2x+5 | | 9x+11=-7x-5 | | 49=10p+-3p | | 12n-23.2=-13n+28.8 | | 3x+1=7+x | | y=-x^2+4 | | y=-x^2+4vertex | | 3b^2=8b | | .5(y-18)=-2 | | 10x=5(x+8) | | 12x+6=18X+1 | | -5x+3y=3 | | -45=x-6x-10 | | 2x+3(6x-3)=151 | | 3(2x-3)=3 | | 18x^2-11x=0 | | -7x+3=-38 | | -7x+3=-5 |